(untitled) (MAUSAM, 1966)
During the International Indian Ocean Expedition, an extensive series of time-lapse motion pictures of clouds was taken from aircraft over the Arabian Sea. An unusual feature revealed by these pictures is the occurrence, during the monsoon season, of cumulus clouds immersed in a dense haze, which frequently cut down the visibility to less than 10 km. In this paper, an attempt is made to explain the occurrence of the haze, over the eastern portions of the Arabian Sea, in terms of condensation of water vapour on sea-salt particles.